To be or not to be: a cross-sectional study on suicidal ideation, intensity of suicidal ideation and suicide attempts among medical students in Kerala, India - Sangeetha Merrin Varghese; Nikhil V Paulson; Pranathi Ajayan; Jithin Mathew Abraham; Pramod Thomas; Anoop Ivan Benjamin; George Chandy Matteethra (BMJ Public Health)
Background India has one of the world’s largest medical consortiums. It has also shown an increasing trend in suicide rates among the medical fraternity in recent years. Recognising the bio-psychosocial context in which suicidal ideation and suicide attempts emerge are important steps in reducing the likelihood of suicide. However, the country lacks a comprehensive national programme to prevent suicidal deaths among medical students. It has become an important public health problem. This study aims to find the proportion of medical students with suicidal ideation and suicide attempts and to explore the factors associated with suicidal ideation in Kerala, India.Methods A cross-sectional study was conducted among undergraduate medical students from all 14 districts of the Kerala state of India. An online survey was conducted, and data was collected from government and private medical colleges across the state. A total of 1102 students participated in the survey, which used the Columbia Suicide Severity Rating Scale.Results The lifetime prevalence of suicidal ideation among medical students was 33.7% (30.88 to 36.54), and those with recent suicidal ideation were 15.2% (13.17 to 17.51). Those who had active suicidal ideation with specific plans were 5.4% (4.18 to 6.95), which puts them at 16 times higher risk of suicide when compared with their counterparts without suicidal ideation. Academic stress, parental pressure in deciding career choices, feelings of discrimination by peers and teachers, and family history of attempted suicide emerged as the key factors associated with suicidal ideation.Conclusion Suicidal ideation precedes suicide. Our research indicates that a significant portion, specifically one-third, of undergraduate medical students in Kerala are grappling with suicidal ideation. This situation calls for immediate, comprehensive interventions at a national scale aimed at tackling the myriad factors contributing to suicidal ideation among medical students.